Conceptions about evaluation in medical education: a path to transformation - Linares-Mendoza, Gerardo; Figueroa-Avendaño, Carlos E.; Rincón-Salazar, Adriana Marcela; Alba-Vásquez, John Alexander (Spanish Journal of Medical Education, 2022)
It has been described that teachers' conceptions determine their educational practice.Evaluation can influence the success or failure of students in school. For this reason, teachers'conceptions of evaluation are important to guide their professional development and evaluativepractice. The purpose of this investigation was to identify and categorize the conceptions aboutevaluation in a group of 14 Medical Education master students at a Colombian university duringan evaluation course. Qualitative research was carried out with thematic analysis of the writteninformation collected at the beginning, during, and at the end of the evaluation course. Prior to theanalysis of the documents, the signing of the informed consent by the participants and compliancewith the ethical requirements of research in humans were guaranteed. It was identified that thepreconception about evaluation was focused on the grade. During the course, this preconceptionevolved towards a holistic conception, immersed in the teaching-learning process in whichmultiple actors and resources are involved, and with a clearly formative purpose. For this reason,the documentation of the conceptual transformation on evaluation highlights the need for formaltraining in evaluation focused on health teachers.